The Role of Bronchoalveolar Lavage in Therapeutic Antimicrobial Choices for Hematologic Patients with Pulmonary Infiltrates - Filippo Patrucco; Mattia Bellan; Davide Martinotti; Giuseppe Ielo; Paola Rebecca Iovine; Martina Mascheroni; Francesco Todisco; Martina Ubaldi; Nadia Castaldo; Francesco Gavelli; Alberto Fantin (Medicina)
Background and Objectives: Lower respiratory tract infections are particularly frequent in hematological patients; their early diagnosis and the timely start of targeted therapy are essential. Bronchoalveolar lavage (BAL) can provide a microbiological sample from the lower airways in a minimally invasive way. This study aimed to determine the diagnostic yield of BAL in hematological patients for microbiological purposes and its influence on modifying the therapeutic strategy. Material and Methods: This multicenter, retrospective, observational study included data from 193 consecutive patients from two centers from January 2020 to October 2022. The patients underwent a bronchoscopy with BAL in cases of pulmonary infiltrates suspicious of pulmonary infection. The demographic data, presenting symptoms, level of immunosuppression, chest CT changes, BAL sampling results, and antimicrobiological drug administration were analyzed. Results: Of the 193 procedures, 143 (74.1%) were performed on hospitalized patients, while 50 were performed on outpatients. In 53.9% of the cases, the BAL isolated at least one germ; in particular, if the procedure was carried out within 72 h of presenting symptoms, the probability of isolating the germ increased significantly (74.3%, p = 0.04). Among the isolated germs, 59.4% were viruses, 28.6% were bacteria, and 12% were fungi. The patients with higher immunosuppression and the febrile ones underwent BAL earlier than the patients with mild immunosuppression (p = 0.01) and those with other presenting symptoms (p = 0.0001). BAL positivity led to a change in empirical antimicrobial therapy in 79 out of 104 cases (77% vs. 36.3%; p < 0.001); these data were also confirmed among the hospitalized patients (81% vs. 44%; p < 0.001). The isolation of a pathogen through BAL and the degree of patient immunosuppression negatively influenced patient survival (p < 0.05 and p < 0.01, respectively). Conclusions: BAL is confirmed as a valid approach for evaluating pulmonary infiltrates in hematological patients, given the excellent clinical impact and high diagnostic yield, mainly if performed early after symptom presentation. However, ongoing antimicrobial treatments at the time of BAL may have potentially affected the diagnostic yield of the procedure.